Is 'starting on time' useful (or useless) as a surrogate measure for 'surgical theatre efficiency'? - Pandit, J; Abbott, T; Pandit, M; Kapila, A; Abraham, R (2012)
We analysed more than 7000 theatre lists from two similar UK hospitals, to assess whether start times and finish times were correlated. We also analysed gap times (the time between patients when no anaesthesia or surgery occurs), to see whether these affected theatre efficiency. Operating list start and finish times were poorly correlated at both hospitals (r 2 = 0.077 and 0.043), and cancellation rates did not increase with late starts (remaining within 2% and 10% respectively at the two hospitals). Start time did not predict finish time (receiver operating curve areas 0.517 and 0.558, respectively), and did not influence theatre efficiency (∼80-84% at either hospital). Median gap times constituted just 7% of scheduled list time and did not influence theatre efficiency below cumulative gap times of less than 15% scheduled list time. Lists with no gaps still exhibited extremely variable finish times and efficiency. We conclude that resources expended in trying to achieve prompt start times in isolation, or in reducing gap times to under ∼15% of scheduled list time, will not improve theatre productivity. Instead, the primary focus should be towards quantitative improvements in list scheduling. © 2012 The Association of Anaesthetists of Great Britain and Ireland.